Studies on the effects of superficial strengthening with FRCM system on compressive strength of AAC masonry - Drobiec, Łukasz; Mazur, Wojciech; Jokiel, Remigiusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
This paper describes results from studies on the effects of superficial strengthening with FRCM system on compressive strength of autoclaved aerated concrete (AAC) masonry. Tests were carried out on models without any strengthening, strengthened at one or both sides. Two-side strengthened masonry demonstrated an increased compressive strength and deformability. Increased deformability was observed for one-side strengthened masonry when compared to tests on masonry without any strengthening.